Recent research progress on the synthesis and biological effects of selenium nanoparticles - Zhang, Ting; Qi, Meng; Wu, Qian; Xiang, Peng; Tang, Dejian; Li, Qiang (Frontiers in Nutrition, 2023)
Selenium is an essential trace element for the human body, with the chemical and physical characteristics of both metals and nonmetals. Selenium has bioactivities related to the immune system, antioxidation, anti-virus, and anti-cancer. At the same time, it also plays a role in reducing and alleviating the toxicity of heavy metals. Compared with inorganic selenium, organic selenium is less toxic and has greater bioavailability. Selenium nanoparticles have the advantages of high absorption rate, high biological activity, and low toxicity, and can be directly absorbed by the human body and converted to organic selenium. Selenium nanoparticles have gradually replaced the traditional selenium supplement and has broad prospects in the food and medical industries. In this paper, the chemical, physical, and biological methods for the synthesis of selenium nanoparticles are reviewed, and the microbial synthesis methods of selenium nanoparticles, the effects of selenium nanoparticles on crop growth, and the antibacterial, antioxidant, anticancer, and anti-tumor effects of selenium nanoparticles are also systematically summarized. In addition, we evaluate the application of selenium nanoparticles in selenium nutrition enhancement, providing support for the application of selenium nanoparticles in animals, plants, and humans.